2020
DOI: 10.1039/d0ra07219b
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, chemical components and pharmacological activities of the genus Ganoderma P. Karst.: a review

Abstract: In recent years, some natural products isolated from the fungus of the genus Ganoderma have been found to have anti-tumor, liver protection, anti-inflammatory, immune regulation, anti-oxidation, anti-viral, anti-hyperglycemic and anti-hyperlipidemic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 94 publications
0
41
0
1
Order By: Relevance
“…They are most popular in Asia, especially in the field of Traditional Chinese Medicine (TCM). These species are also used traditionally in some West African countries, such as Nigeria, for treating skin diseases, hypertension, and digestive disorders [ 2 , 3 ]. Scientific research has confirmed the broad-spectrum effects of isolated compounds and extracts from Ganoderma spp., e.g., antitumor, immunomodulatory, antioxidant, anti-inflammatory, antiallergic, neuroprotective, hepatoprotective, hypoglycemic, hypotensive, antimicrobial, antiviral, and antimalarial effect [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are most popular in Asia, especially in the field of Traditional Chinese Medicine (TCM). These species are also used traditionally in some West African countries, such as Nigeria, for treating skin diseases, hypertension, and digestive disorders [ 2 , 3 ]. Scientific research has confirmed the broad-spectrum effects of isolated compounds and extracts from Ganoderma spp., e.g., antitumor, immunomodulatory, antioxidant, anti-inflammatory, antiallergic, neuroprotective, hepatoprotective, hypoglycemic, hypotensive, antimicrobial, antiviral, and antimalarial effect [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma is not only a famous Chinese medicine, it is also used globally as a food, in the form of tea, coffee and other beverages, and in syrups and dietary supplements ( Wang et al, 2020 ; Kumar, 2021 ). Polysaccharides and triterpenoids are representative of the important biologically active components of Ganoderma ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma is not only a famous Chinese medicine, it is also used globally as a food, in the form of tea, coffee and other beverages, and in syrups and dietary supplements ( Wang et al, 2020 ; Kumar, 2021 ). Polysaccharides and triterpenoids are representative of the important biologically active components of Ganoderma ( Wang et al, 2020 ). Recent ongoing research studies exploring Ganoderma demonstrated that it contains meroterpenoid components that possess extensive biological activities, such as renal protection and neuroprotection, anti-inflammation, -tumor and -oxidation properties, and analgesic effects ( Jiang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 These compounds have significant anti-oxidation, liver protection, anti-cancer, anti-virus, immune regulation and other effects. [9][10][11] Therefore, identifying the species of wild mushrooms plays an important role in food safety and value evaluation.…”
Section: Introductionmentioning
confidence: 99%